African American Vernacular English (AAVE) Used by Rich Brian: A Sociolinguistic Investigation - Aryani, Intan Tia Ajeng (Universitas Negeri Semarang, 2020)
The author investigated the use of AAVE by Brian Imanuel or Rich Brian in his rap song lyrics. This study aimed to identify the grammatical features of AAVE in Brian's Amen album. Further, this study was also explored the underlying effect on Brian's use of AAVE. This study applied a descriptive-qualitative method. The context of the data in this study was song lyrics. The results are as follows: Brian rap song lyrics' contained 7 out of AAVE's 13 grammatical features. Those areÃ‚Â copula absence, invariant be, completive done, specialized auxiliaries, negation, nominal,Ã‚Â andÃ‚Â ain't. The causal effect on the use of AAVE by Brian is influenced by the environment or neighborhoods where he grew up. Growing up around his friends who use AAVE in their daily conversation leads him to obtain AAVE's native-like control. Likewise, AAVE's use was the main effect of the linguistic marketplace in order to project identities in stable ways.